FAKTOR – FAKTOR YANG MEMPENGARUHI PENGGUNAAN JASA JOKI TUGAS OLEH PELAJAR DAN MAHASISWA - Elizabeth Amelia Permata Sari; Daniel Jefri Kurniawan (KOLONI, 2023)
This research aims to explore the factors that influence the use of task-jockeying services by students. The method used is qualitative research by conducting in-depth interviews and observations on 10 students who use task-jockeying services. The results of the study show that the use of task-jockeying services by students is influenced by factors such as time constraints, difficulty in doing tasks, lack of ability in subject matter, excessive task loads, and easy access. Some of these factors may be related to each other, such as excessive task loads that can lead to difficulty in doing tasks and a lack of ability in subject matter. However, it is important for students to consider the impact of using task-jockeying services on their academic ethics and the long-term implications of such actions. This research is expected to provide a clearer picture of the use of task-jockeying services by students and help students make better decisions about using these services to improve their academic performance.  Keywords: Factors, Influence, Task-Jockeying Services, Students.